(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2012)
The aqueous leaves extract of Prosopis cineraria (AEPC) is used traditionally for the treatment of various CNS disorder. The purpose of this study was to evaluate the extract for antidepressant and skeletal muscle relaxant activity. The antidepressant effect of the extract was evaluated using Forced swim test (FST). The immobility periods of control and treated mice were recorded. The antidepressant-like effect of tested compound was compared to that of imipramine (15 mg/kg. p.o). Muscle relaxant property was studied using rotarod apparatus and total fall off time for standard and control group was recorded. Phytochemical screening revealed the presence of saponins, flavonoids, alkaloids, glycosides, tannins and phenolic compounds. The leaf extract at doses of 200 mg/kg significantly decreased the duration of immobility time in FST. The efficacy of tested extract was found to be comparable to that of imipramine. Our results suggested that the aqueous extract of Prosopis cineraria leaves exerts antidepressant-like effect.